Macro-Fiscal Implications of Climate Change : The Case of Djibouti - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2018)
This paper reviews the significant macro-fiscal challenges posed by climate change in Djibouti and the costs of mitigation and adaptation policies. The paper concludes that Djibouti is susceptible to climate change and related costs are potentially large. Investing now in adaptation and mitigation has large benefits in terms of reducing the related costs in the future. Reforms to generate the fiscal space are therefore needed and investment for mitigation and adaptation to climate change should be built into the long-term fiscal projections. Finally, concerted international efforts and stepping up regional cooperation could help moderate climate-related macro-fiscal risks.